Radiotherapy target volume definition in newly diagnosed high grade glioma using 18F-FET PET imaging and multiparametric perfusion MRI: A prospective study (IMAGG) - Dissaux, Gurvan; Dissaux, Brieg; Kabbaj, Osman El; Gujral, Dorothy M.; Pradier, Olivier; Salaün, Pierre-Yves; Seizeur, Romuald; Bourhis, David; Ben Salem, Douraied; Querellou, Solène; Schick, Ulrike (Radiotherapy and Oncology, 2020)
•First prospective study comparing spatial differences between multiparametric perfusion MRI and FET PET•Multiparametric perfusion MRI volumes are highly correlated with CE T1 gadolinium volumes.•FET PET suggests that the metabolically tumor is underestimated by contrast enhanced MRI.•rCBV hot spot could be used to identify subvolume with increased neoangiogenesis. The aim of this study was to prospectively investigate tumor volume delineation by amino acid PET and multiparametric perfusion magnetic resonance imaging (MRI) in patients with newly diagnosed, untreated high grade glioma (HGG). Thirty patients with histologically confirmed HGG underwent O-(2-[18F]-fluoroethyl)-l-tyrosine (18F-FET) positron emission tomography (PET), conventional Magnetic Resonance Imaging (MRI) as contrast-enhanced (CE) and fluid-attenuated inversion recovery (FLAIR) and multiparametric MRI as relative cerebral blood volume (rCBV) and permeability estimation map (K2). Areas of MRI volumes were semi-automatically segmented. The percentage overlap volumes, Dice and Jaccard spatial similarity coefficients (OV, DSC, JSC) were calculated. The 18F-FET tumor volume was significantly larger than the CE volume (median 43.5 mL (2.5–124.9) vs. 23.8 mL (1.4–80.3), p = 0.005). The OV between 18F-FET uptake and CE volume was low (median OV 0.59 (0.10–1)), as well as spatial similarity (median DSC 0.52 (0.07–0.78); median JSC 0.35 (0.03–0.64)). Twenty-five patients demonstrated both rCBV and CE on MRI: The median rCBV tumor volume was significantly smaller than the median CE volume (p < 0.001). The OV was high (median 0.83 (0.54–1)), but the spatial similarity was low (median DSC 0.45 (0.04–0.83); median JSC 0.29 (0.07–0.71)). Twenty-eight patients demonstrated both K2 and CE on MRI. The median K2 tumor volume was not significantly larger than the median CE volume. The OV was high (median OV 0.90 (0.61–1)), and the spatial similarity was moderate (median DSC 0.75 (0.01–0.83); median JSC 0.60 (0.11–0.89)). We demonstrated that multiparametric perfusion MRI volumes (rCBV, K2) were highly correlated with CE T1 gadolinium volumes whereas 18F-FET PET provided complementary information, suggesting that the metabolically active tumor volume in patients with newly diagnosed untreated HGG is critically underestimated by contrast enhanced MRI. 18F-FET PET imaging may help to improve target volume delineation accuracy for radiotherapy planning.